Utilization of Biochar from Catalytic Pyrolysis of Mixed Biomass Waste for Bio Briquette Production - Muhammad Waskito; Christina May Putri Cahyaningrum; Selvia, Dewi; Prasetiawan, Haniif; Bahlawan, Zuhriyan Ash Siddieqy (Universitas Negeri Semarang, 2024)
The increasing depletion of fossil fuel reserves and the need for sustainable energy alternatives have accelerated research on biomass-based briquettes. This study investigates the effect of different catalyst types (6% zeolite, 6% activated carbon, and no catalyst) and binder concentrations (5%, 10%, and 15% w/w) on the physicochemical properties of bio briquettes derived from a mixture of sugarcane bagasse, palm empty fruit bunches (TKKS), and rice husk. Key performance parameters analyzed include moisture content, ash content, and calorific value. The lowest moisture content (2.1%) was obtained using 6% zeolite with 15% binder, while the lowest ash content (5%) was recorded using 6% activated carbon with 5% binder. In terms of energy potential, the highest calorific value (4431.42 cal/g) was achieved with 6% zeolite and 5% binder. However, none of the samples met the SNI 01-6235-2000 calorific value standard (>5000 cal/g), though all met the ESDM minimum threshold (>3500 cal/g), indicating their potential for domestic use. Statistical analysis revealed a quadratic relationship between binder concentration and both moisture and calorific value, highlighting the importance of formulation optimization. The results demonstrate that catalyst type and binder concentration play a critical role in determining the quality of bio briquettes, and a balance between low moisture, minimal ash, and high calorific value must be achieved for practical application. This study supports the development of eco-friendly and renewable solid fuels as a viable substitute for fossil fuels in household energy needs.